Prevalence And Risk Factors of Malnutrition Among Women of Reproductive Age In Bangladesh: A Secondary Data Analysis of Bdhs 2022 (Bioresearch Communications, 2024)
Background/Objective: Women of reproductive age (WRA) in developing countries experience a double burden of malnutrition, which adversely impacts their health and the well-being of future generations. Addressing this issue requires updated data to guide effective interventions. Therefore, this study aimed to assess the prevalence and factors associated with malnutrition among WRA in Bangladesh using recent national data.Methodology: This study analyzed data from the Bangladesh Demographic and Health Survey (BDHS)-2022, which included a nationally representative sample of 8,593 WRA between 15 and 49 years. The outcome variables were malnutrition: underweight (BMI< 18.5 kg/m2), overweight (BMI 23 to